The digital crown - Leibtag, Ahava (Morgan Kauffmann is an imprint of Elsevier, 2014)
In 1997, Bill Gates famously said "Content is king." Since then, the digital marketing world has been scrambling to fulfill this promise, as we finally shift our focus to what consumers really want from our brands: a conversation.The Digital Crown walks you through the essentials of crafting great content: the fundamentals of branding, messaging, business goal alignment, and creating portable, mobile content that is future-ready. Systems create freedom, and within this book you'll learn the seven critical rules to align your internal and external content processes, including putting your audience first, involving stakeholders early and often, and creating multidisciplinary content teams